The Role of Partnerships in Supporting COVID-19 Vaccine Uptake Among Migrants: A Qualitative Case Study from Tamil Nadu and Punjab, India - Ankita Meghani; Bharathi Palanisamy; Sunita Singh; Tanya Singh; Natasha Kanagat; Anil Gupta; Kapil Singh; Gopal Krishna Soni (Vaccines)
Background: During the COVID-19 pandemic, migrant populations remained under-immunized due to limited access to health care, language barriers, and vaccine hesitancy. The USAID-funded MOMENTUM Routine Immunization Transformation and Equity project supported the government in collaborating with various local health and non-health partners to identify and vaccinate migrants. This case study examines the roles of project partners and the strategies each entity implemented to increase COVID-19 vaccine uptake among migrants, as well as the perceptions regarding the effectiveness of these strategies. Methods: We designed a qualitative explanatory case study guided by the Behavioral and Social Drivers framework and RE-AIM implementation science frameworks. We conducted 31 focus group discussions and 50 in-depth interviews with migrants, project partners, community leaders, and government stakeholders in Tamil Nadu and Punjab. Results: In both states, partnerships with health departments, private employers, and community-based organizations were essential for identifying and vaccinating un- and under-vaccinated migrant groups. In Tamil Nadu, collaboration with the Department of Labor and mobile medical units facilitated vaccination camps at construction sites. In Punjab, religious institutions organized sessions at places of worship, and the Border Security Force enabled health workers to reach migrants living near the border. In both states, key strategies—involving influencers to discuss the importance of vaccine safety and value, bringing vaccination services to migrants’ workplaces and homes at flexible times and mandating workplace vaccination to encourage vaccination—shifted perceptions towards vaccination and increased vaccine uptake among migrants. Conclusions: The strategies and partnerships identified in this study highlight the broader implications for future public health interventions, demonstrating that collaboration with the private sector and faith-based organizations can enhance routine immunization efforts, particularly when localized to organizations that understand community needs and can address specific barriers and motivators.